2021
DOI: 10.3390/ijerph18094760
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Echelon Network Design in a Dual-Channel Reverse Supply Chain Considering Consumer Preference

Abstract: The rapid development of e-commerce technologies has encouraged collection centers to adopt online recycling channels in addition to their existing traditional (offline) recycling channels, such the idea of coexisting traditional and online recycling channels evolved a new concept of a dual-channel reverse supply chain (DRSC). The adoption of DRSC will make the system lose stability and fall into the trap of complexity. Further the consumer-related factors, such as consumer preference, service level, have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…For instance, the pressure to accept Amazon return policies to be an Amazon seller or equivalent in other platforms that, in some way, have forced companies to accept a higher volume of returns (D'Agostino, 2018; Watanabe et al, 2021). Both environmental and legislative pressures have forced companies to take end-of-life products contributing to an increasing wave in the reverse logistics channel (Li & Wu, 2021;Calzolari et al, 2021).…”
Section: Figure 10mentioning
confidence: 99%
“…For instance, the pressure to accept Amazon return policies to be an Amazon seller or equivalent in other platforms that, in some way, have forced companies to accept a higher volume of returns (D'Agostino, 2018; Watanabe et al, 2021). Both environmental and legislative pressures have forced companies to take end-of-life products contributing to an increasing wave in the reverse logistics channel (Li & Wu, 2021;Calzolari et al, 2021).…”
Section: Figure 10mentioning
confidence: 99%
“…By introducing consumer preference for the online recycling channel, Sana (2022c) indicated that the demand rates of traditional and online consumers are segregated from the total capacity of the market. Li and Wu (2021) designed a multi-echelon network in a dual-channel recycling supply chain considering consumer preference. Kang et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By introducing consumer preference for the online recycling channel, Sana (2022c) indicated that the demand rates of traditional and online consumers are segregated from the total capacity of the market. Li and Wu (2021) designed a multi-echelon network in a dual-channel recycling supply chain considering consumer preference. Kang et al (2020) found that the change in consumer preference for online channels in a certain region affects the decisions and profits of multi-regional recycling enterprises.…”
Section: Impact Of Consumer Types On Recycling Supply Chain Managementmentioning
confidence: 99%
“…Jin et al [ 30 ] analyzed the influence of the power structure on the pricing decisions and profits of remanufacturers and recyclers in a DRSC. By incorporating consumers’ preference for online recycling channels into the system, Li and Wu [ 31 ] conducted research on the strategic network design of a DRSC and constructed a detailed quantitative model for network design optimization.…”
Section: Literature Reviewmentioning
confidence: 99%